Review of Archaeologies of Memory - Ajay Pratap (Ancient Asia, 2015)
This is a review of the above work which analyses the nature, means and ways of remembering, and perhaps even the purpose of remembering, in past societies. As such, this is a very intelligent and thought-provoking work.